ABOUT THE APPROACH AND METHOD OF DETERMINING THE VALUE OF ROYALTIES FOR THE DEVELOPMENT OF MINERALS - V. M. Serov (Publishing House of the State University of Management, 2019)
All business entities, regardless of their form of ownership, must obey established rules, when paying for the right to use licenses for inventions, renting films, publishing books, products, patents, innovations. The calculation of the amount of payment is carried out in accordance with the bilateral agreement. Calculating royalties, based on profits earned by an enterprise, has certain disadvantages. Many of the most diverse factors affect the volume of profit. The author’s approach and the method of determining the value of royalties for the development of mineral resources have been explained in the article. Their basis consists of: determining the value of economic rent as a result of the extraction and sale of mineral resources; ensuring, that mining companies receive income on their production capital at a level not lower than the average for the country’s economy as a whole.